Behavioral manipulation of Ixodes scapularis by Ehrlichia muris eauclairensis: implications for tick-borne disease transmission - Joseph Aspinwall; Barbara Weck; Larissa A. Martins; Clayton Jarrett; Motoshi Suzuki; Mina P. Peyton; Daniel E. Sonenshine; Tais B. Saito (mBio, 2025)
ABSTRACT Tick-borne diseases pose significant risks to both animals and humans, with emerging pathogens like Ehrlichia muris eauclairensis (EME) underscoring the need for a deeper understanding of pathogen-vector interactions and tick fitness. This study investigates the impact of EME on Ixodes scapularis nymphs, revealing significant behavioral changes in EME-positive ticks. These ticks exhibited increased movement speed, faster bite site-seeking for attachment, and prolonged feeding durations compared to control ticks. Proteomic analyses of the tick synganglion during resting and feeding phases identified 196 differentially expressed proteins in EME-positive ticks, including multiple proteins associated with nicotinic acetylcholine signaling pathways. Our findings indicated altered neuropeptide expression related to stimulus response and activity, suggesting changes in neurophysiology. This research provides the first evidence of behavioral manipulation by an Ehrlichia species, indicating that the tick nervous system is a site of bacterial influence and a potential target for interventions. These findings offer new insights into pathogen-vector dynamics that could lead to the development of transmission-blocking therapies, significantly impacting tick fitness and disease transmission.IMPORTANCETick-borne diseases (TBDs) are increasingly affecting humans, pets, and livestock, with cases rising in recent years. Ticks can carry multiple harmful germs, and human activities and environment are contributing to new TBDs. This study shows that the bacteria Ehrlichia muris eauclairensis (EME) can change the behavior of nymphal black-legged ticks, which spread various diseases. Infected ticks moved faster, attached to hosts more quickly, and fed longer than uninfected ticks. These changes were linked to specific proteins in the tick’s nervous system, suggesting that EME manipulates tick behavior. This is the first evidence that an Ehrlichia species can influence tick behavior, potentially increasing disease transmission. Understanding these interactions can help develop strategies to prevent TBDs by targeting the bacteria’s influence on ticks, ultimately reducing disease spread and improving public health.